Pengembangan Media Pembelajaran Interaktif Kompetensi Dasar Register Berbasis Inkuiri Terbimbing - Muhammad Munir (Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
The objective of this study was to develop interactive learning media for the basic competency of Register Based on Guided Inquiry that can be utilized as learning media for the students. The study was conducted using the Research and Development method. The experiment was performed to determine the functions of navigation buttons of the media.The result of this study showed that all navigation functions operate properly with the percentage of 100 %.